A critical look at the new possibilities of therapeutic use of statins – a summary of the current state of knowledge - Kacper Kossakowski; Klaudia Katarzyna Orzechowska; Weronika Sikora; Wiktoria Grabowska; Kornelia Kowalska; Radosław Kujawski; Kamila Czora-Poczwardowska; Michał Szulc; Przemysław Łukasz Mikołajczak; Joanna Bartkowiak-Wieczorek (Farmacja Polska, 2023)
Hypercholesterolemia is a condition characterized by total cholesterol levels exceeding 200 mg/dl. A breakthrough in its treatment was the introduction of the first representative of the status - lovastatin. The mechanism of their action relies on inhibition of the activity of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, the enzyme responsible for converting HMG-CoA to mevalonic acid, the main substrate in the synthesis of endogenous cholesterol. The progress of experimental and clinical studies on action statins indicates a number of other biological properties of this group of compounds, and thus their pharmacological potential. The possibility of their use in the pharmacotherapy of cardiovascular diseases, hyperandrogenism in women with polycystic ovary syndrome (PCOS), osteoporosis, type 2 diabetes, neurodegenerative diseases, or cancer has been so far highlighted. The aim of this paper was to systematize the knowledge of statin drugs in terms of the progress of studies on their biological activity indicating the possibility of their potential use in the treatment of diseases other than those related to the cardiovascular system, along with verification of their safety profile and demonstrated adverse effects (DN) as a result of their intake. The literature review was conducted by a screening of the following scientific databases - PubMed and Google Scholar (the analysis lasted from March 2022 to February 2023). The keywords used for searching were disease-related and DN-related. Statins have shown potential to alleviate symptoms of androgen excess in women suffering from polycystic ovary syndrome (PCOS). Studies relating to their effect on the treatment of Alzheimer's disease and dementia indicate a reduction in progressive neurodegenerative changes, and thus suggest their potential use in the prevention and treatment of comorbid cardiovascular disease. Moreover, statins tend to reduce morbidity, increase survival, and alleviate the progression of cancer. The results of studies of the effects of these drugs on the possibility or development of Parkinson's disease, osteoporosis and the etiology of muscle symptoms appear to be inconsistent in the relationship of their benefits to DN. Unfortunately, it seems that they have also led to disturbances in carbohydrate metabolism and increased the risk of type II diabetes mellitus (NODM). Studies on the effect of the nocebo effect during statin therapy on the frequency with which patients experience DN have confirmed the presence of this effect. Analysis of the collected studies shows considerable potential for expanding the current therapeutic indications of the drugs in question. However, further randomized controlled trials are required to determine the precise effective dose, duration of therapy for a specific statin.